2019
DOI: 10.6115/fer.2019.036
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Internal Locus of Control in the Relationship between Family and Friend Support and Acculturative Stress of North Korean Adolescent Refugees

Abstract: This study examined the mediating effect of internal locus of control in the relationship between family and friend support and acculturative stress of North Korean adolescent refugees. Participants consisted of 101 North Korean adolescent refugees (40 males and 61 females) aged 13 to 24, who live in Seoul, Gyeonggi Province, and Busan. SPSS 25.0 and Mplus 5.12 were used to analyze data. Descriptive statistics and Pearson's correlation coefficients were calculated and structural equation modeling (SEM) examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This is contrary to previous studies, which showed that the perception that support can be gained from relatively close family or peer relationships plays a positive psychological role in the cultural adaptation process [ 23 , 45 , 57 ]. However, according to a study by Jeong and Kang [ 8 ] on environmental protection factors, peer support alone does not have a significant impact on cultural adaptation stress, but can be indirectly influenced by personal internal protection factors such as internal locus of control, suggesting the indirect influence of external factors. Regarding family function, no statistically significant association with changes in depression over time was reported in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is contrary to previous studies, which showed that the perception that support can be gained from relatively close family or peer relationships plays a positive psychological role in the cultural adaptation process [ 23 , 45 , 57 ]. However, according to a study by Jeong and Kang [ 8 ] on environmental protection factors, peer support alone does not have a significant impact on cultural adaptation stress, but can be indirectly influenced by personal internal protection factors such as internal locus of control, suggesting the indirect influence of external factors. Regarding family function, no statistically significant association with changes in depression over time was reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The cultural adaptation stress experienced by NKRYs in the process of settling is a significant factor that makes adapting to South Korean society difficult [ 7 ]. In particular, it is highly likely that they will experience additional stress due to the developmental transition from childhood to adulthood [ 8 , 9 ]. NKRYs are known to experience many psychological symptoms, such as posttraumatic stress disorder, anxiety and depression, delinquency, aggression, and hostile behavior [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation